2022
DOI: 10.3390/ijerph191610047
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in COX2 Is Associated with Persistent Primary Tooth and Delayed Permanent Tooth Eruption

Abstract: Persistent primary tooth (PPT) is a prevalent clinical condition that occurs when a primary tooth is over-retained beyond the established period of its normal exfoliation time, remaining in the oral cavity. Many factors could be involved in the risk of PPT; therefore, the aim of this study was to evaluate if single nucleotide polymorphisms (SNPs) in the COX2 gene are associated with PPT. Children undergoing orthodontic treatment were screened. Orthopantomographs were assessed to evaluate PPT according to the N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Modesto, et al 31 (2019) assessed whether genetic polymorphisms in growth factors ( IGF, FGFs, and FGFRs ) were involved in dental age and observed that FGF18 (rs4073716) was associated with an older dental age than the child’s chronological age. Genetic polymorphisms in the vitamin D receptor (VDR) were not associated with dental age in the study by Küchler, et al 29 (2022), also in Brazilian children.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Modesto, et al 31 (2019) assessed whether genetic polymorphisms in growth factors ( IGF, FGFs, and FGFRs ) were involved in dental age and observed that FGF18 (rs4073716) was associated with an older dental age than the child’s chronological age. Genetic polymorphisms in the vitamin D receptor (VDR) were not associated with dental age in the study by Küchler, et al 29 (2022), also in Brazilian children.…”
Section: Discussionmentioning
confidence: 93%
“…Only a few studies have investigated the role of genetic polymorphisms in dental age in humans. 29 , 31 Understanding the relationship between dental age and genetic polymorphisms can have significant implications for clinical practice. Dental age assessment is a crucial aspect of orthodontic treatment planning, as it helps determine the optimal timing and approach for interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was an option. The results of this study suggest that it may be worthwhile to incur the costs of a similar longitudinal study [23]. Randomized controlled trials (RCTs) have not been conducted in this industry due to recruitment, ethics, and follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…The panoramic radiographs of each patient were assessed by a single examiner, an experienced pediatric dentist (B.G.T.). PPT was defined as a primary tooth that did not exfoliate and the eruption time of the permanent successor tooth had expired for more than one year, as previously described [4,[16][17][18]. The eruption time of the permanent successor tooth was examined based on the chronological scale determined by considering the genders of the Turkish children [19].…”
Section: Determination Of Pptmentioning
confidence: 99%